Evaluation de l’effet gastro protecteur de l’extrait de JUNIPERUS PHOENICEA sur l’ulcère gastrique induit par les AINS (étude expérimentale chez les souris souche NMRI ) - AISSA, Sihem (My University, 2019)
JUNIPERUS PHOENICIA is a medicinal plant, familyCupressaceae, has been widelyused in traditionalmedicine in the treatment of variousdiseases, amongthesediseasesGastriculceris one of the mostseriousdiseases. The objective of thisworkis to evaluate the gastroprotectiveeffect of the juniperus phoenicia extract on the ulcerinduced by NSAIDs:Diclofenac sodium [Votrex®], For thisfact, weadopted a researchexperimental. infemale NMRI strainmice. Macroscopic and microscopicevaluation at the stomachlevels shows that oral administration of diclofenac, sicca has causedgastriclesions in the glandular part of the stomach and the presence of edema .Becausetheselesions are less important in the poisons treatedwith juniperus phoenicia extract,Theseresultssuggestthat the JUNIPERUS PHOENICIA extract has a gastroprotectiveeffect, whichis due to itsability to prevent the formation of lesions, and to induce the protective mechanisms of the gastricmucosathatwouldbe due to itsgastrointestinaleffectpotential. -protective, anti ulcerative and anti-inflammatory1
Keywords: gastriculcer; juniperus phoenicia; NSAIDs; sodium diclofenac; gastroprotectiveeffect; NMRI mice1